Is sleep deprivation involved in domestic violence? - Hoshino, Katsumasa [UNESP] (2009)
background and objective: Sleep deprivation promotes an increase in aggressiveness; however, this effect has not been investigated in humans. Since high alcohol intake promotes desynchronized sleep deprivation and alcoholism is directly associated with domestic violence (DV), this study aimed to collect information on sleep characteristics, anxiety, and alcohol consumption by DV perpetrators. Methods: Having this purpose in mind, 53 female victims of physical violence perpetrated by their intimate partners (DV group) were interviewed after providing free informed consent. The interviews took place on the occasion that the abused women registered a formal accusation at the Specialized Police Station for Women. The interviews were structured in a previously tested questionnaire. Results: Thirty women from the general population without any complaint of DV composed the control group. The DV group showed prevalent insomnia, high sleep fragmentation, intense daily snoring, a tendency to disregard sleep hygiene rules and thus feel sleepy during the day, sleep complaints, high alcohol intake, and high anxiety levels. Increased aggressiveness from their partners after a poor night's sleep was reported by 58% of DV victims, and half of them reported having been battered on those days. Conclusions: Data obtained support the possible involvement of sleep-deprivation-induced aggressiveness in DV etiology; this fact requires confrmation by further studies using other reliable methods.